2022
DOI: 10.3390/jcm11216538
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peripheral Inflammatory Markers in Patients with Acute Headache Attack to Differentiate between Migraine and Non-Migraine Headache

Abstract: Although the potential relationship between headaches, particularly migraine, and peripheral inflammatory markers (PIMs) has been investigated, it is unclear whether PIMs are involved in the pathogenesis of migraine or can differentiate it from non-migraine headaches (nMHs). Using 10 years of data from the Smart Clinical Data Warehouse, patients who visited the neurology outpatient department (OPD) within 30 days after visiting the emergency room (ER) for headaches were divided into migraine and nMH groups, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Researchers believe that body mass index (BMI) may play an important influence. Studies on overweight or obese subjects consistently revealed higher levels of CRP in migraineurs [ 7 , 46 , 47 ]. Conversely, studies with normal-weight or underweight participants generally found no significant CRP differences between migraineurs and healthy controls [ 7 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers believe that body mass index (BMI) may play an important influence. Studies on overweight or obese subjects consistently revealed higher levels of CRP in migraineurs [ 7 , 46 , 47 ]. Conversely, studies with normal-weight or underweight participants generally found no significant CRP differences between migraineurs and healthy controls [ 7 , 48 ].…”
Section: Discussionmentioning
confidence: 99%